2018
DOI: 10.1002/slct.201801155
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Electrochemistry, DFT Calculations, Antimicrobial Properties and X‐ray Crystal Structures of Some NH‐ and/or S‐ Substituted‐1,4‐quinones

Abstract: The NH-, NH-,S-substituted-1,4-naphthoquinones and NH-, Ssubstituted-1,4-benzoquinones have been synthesized from the reaction between quinones (2,3-Dibromo-1,4-naphthoquinone or p-benzoquinone) and different amines. The structures of the compounds have been confirmed using FTIR, UV-Vis, 1 H-NMR, 13 C-NMR, mass MS(ESI) spectrometry and cyclic voltammetry (CV). The ground state energies of the molecules have been estimated using B3LYP functional with different basis sets based on time dependent density function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Recently, various iodine-catalyzed methods to synthesize aromatic thioethers have been successfully developed, wherein oxidants such as tributylphosphate (TBP), dimethyl sulfoxide (DMSO), and H 2 O 2 were necessary for those transformations. On the other hand, there are also reports on the addition of thiols into p -quinones without the use of any catalyst . Among them, 1,4-quinone and thiophenols in methanol or water media at room temperature via the cross-dehydrogenative coupling (CDC) have been achieved in this transformation .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, various iodine-catalyzed methods to synthesize aromatic thioethers have been successfully developed, wherein oxidants such as tributylphosphate (TBP), dimethyl sulfoxide (DMSO), and H 2 O 2 were necessary for those transformations. On the other hand, there are also reports on the addition of thiols into p -quinones without the use of any catalyst . Among them, 1,4-quinone and thiophenols in methanol or water media at room temperature via the cross-dehydrogenative coupling (CDC) have been achieved in this transformation .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, introducing amino substituents into the 1,4‐quinone moiety, named aminoquinones, significantly improves biological properties which are of great importance in pharmaceutical chemistry (Egleton et al, ; Pingaew et al, ; Prachayasittikul et al, ; Xu et al, ). Aminoquinones are generally synthesized by the (a) reaction of hydroquinone and amines (Ikeda, Wakabayashi, & Nakane, ; Niedermeyer, Mikolasch, & Lalk, ), (b) nucleophilic addition reactions of 1,4‐quinones with amines (Ryu et al, ; Valderrama et al, ), and (c) nucleophilic substitution reactions of the methoxy or halogen derivative of 1,4‐quinones with amines in different media (Delarmelina et al, ; Kacmaz et al, ; Pingaew et al, ; Ryu, Nho, Jin, Oh, & Choi, ; Tandon, Kumar, Mishra, & Shukla, ; Tandon & Maurya, ).…”
Section: Introductionmentioning
confidence: 99%
“…The increase in the number of studies on this subject is not surprising. In this context, it is no surprise that recent studies contain these activity increasing substituents (4,5). Recently Errante et al reported that some thio derivatives of naphthoquinones exhibited better activities than amphotericine B against some fungi (6).…”
Section: Introductionmentioning
confidence: 99%